Galaxy clustering in harmonic space from the dark energy survey year 1 data: compatibility with real-space results. Issue 4 (10th June 2021) - Andrade-Oliveira, F; Camacho, H; Faga, L; Gomes, R; Rosenfeld, R; Troja, A; Alves, O; Doux, C; Elvin-Poole, J; Fang, X; Friedrich, O; Kokron, N; et al.
ABSTRACT: We perform an analysis in harmonic space of the Dark Energy Survey Year 1 Data (DES-Y1) galaxy clustering photometric data using products obtained for the real-space analysis. We test our pipeline with a suite of lognormal simulations, which are used to validate scale cuts in harmonic space as well as to provide a covariance matrix that takes into account the DES-Y1 mask. We then apply this pipeline to DES-Y1 data taking into account survey property maps derived for the real-space analysis. We compare with real-space DES-Y1 results obtained from a similar pipeline. We show that the harmonic space analysis we develop yields results that are compatible with the real-space analysis for the bias parameters. This verification paves the way to performing a harmonic space analysis for the upcoming DES-Y3 data.